Drug Stock Optimization at Hospital Depot Using Shuffle Frog Leaping Algorithm (SFLA) - Ghazalba, Annazma; Mulyo Widodo, Agung; Tjahjono, Budi; Firmansyah, Gerry (Pelopor Publikasi Akademika, 2024)
Optimal, efficient, and accurate drug stock management at hospital depots is crucial for ensuring the smooth operation of medical and operational services. Therefore, the use of machine learning is currently essential for managing drug stocks at hospital depots more optimally. This optimization process involves stages such as data collection, data pre-processing, attribute selection, data labeling, classification algorithm selection, model training, model eval_uation, and result interpretation. The data used in this research includes information on drug stocks at hospital depots with details on drug items, quantities, prices, depot origins, demand trends, and types of transactions. The aim of using these algorithms is to classify drug stock items into categories such as